Kepemimpinan Geuchik, Partisipasi Masyarakat dan Kompetensi Perangkat Gampong terhadap Efektivitas Pelayanan Publik (Studi pada Kantor Geuchik Keurisi Meunasah Beureumbang Kecamatan Jangka Buya Pidie Jaya) - Alfurqan Alfurqan; Endang Syahriani; Murni Murni; Mirza Mirza (Singkite Journal, 2025)
The study aims to analyze the effectiveness of public services from the impact of Geuchik leadership, community participation, and the competence of village officials. Using quantitative associative research using regression analysis. The study was conducted on 234 residents of Gampong Keurisi Meunasah Beureumbang, Jangka Buya District, Pidie Jaya Regency. The results showed that there were effects; (1) each factor of Geuchik leadership, community participation, and the competence of village officials on the effectiveness of public services at the Geuchik Office. (2) And the biggest impact was the community participation factor. (3) simultaneously, the three factors contributed to the effectiveness of public services by 75.8%.